Markov Perfect Equilibrium Advertising Strategies of Lanchester Duopoly Model: A Technical Note - Jarrar, Ramla; Martín-Herrán, Guiomar; Zaccour, Georges (Management Science, 2004)
We propose a numerical approach to compute stationary Markov perfect Nash equilibrium advertising strategies of the Lanchester model. The algorithm can be implemented using a standard mathematical package, and, importantly, it does not require that the players discount their future earnings at a zero rate, an assumption that has been made in the literature.